2015
DOI: 10.6061/clinics/2015(05)13
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan extension and increased resistance to environmental stressors by N-Acetyl-L-Cysteine in Caenorhabditis elegans

Abstract: OBJECTIVE:This study was performed to determine the effect of N-acetyl-L-cysteine, a modified sulfur-containing amino acid that acts as a strong cellular antioxidant, on the response to environmental stressors and on aging in C. elegans.METHOD:The survival of worms under oxidative stress conditions induced by paraquat was evaluated with and without in vivo N-acetyl-L-cysteine treatment. The effect of N-acetyl-L-cysteine on the response to other environmental stressors, including heat stress and ultraviolet irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 50 publications
6
55
0
Order By: Relevance
“…N-acetyl-L-cysteine, a sulfur-containing cysteine derivative with an acetyl group attached to the nitrogen of cysteine, has anti-oxidant and anti-cancer activity (Cai et al, 1999;Yedjou & Tchounwou, 2007). Survival of worms after heat shock or UV irradiation significantly increases by pre-treatment with 5 mM N-acetyl-L-cysteine (Dh et al, 2015). Dur data showed that A. annua can specifically modulate the response to heat stress, however has no effect on resistance to UV irradiation.…”
Section: Effect Of a Annua On Response To Heat Shock And Uv Irradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…N-acetyl-L-cysteine, a sulfur-containing cysteine derivative with an acetyl group attached to the nitrogen of cysteine, has anti-oxidant and anti-cancer activity (Cai et al, 1999;Yedjou & Tchounwou, 2007). Survival of worms after heat shock or UV irradiation significantly increases by pre-treatment with 5 mM N-acetyl-L-cysteine (Dh et al, 2015). Dur data showed that A. annua can specifically modulate the response to heat stress, however has no effect on resistance to UV irradiation.…”
Section: Effect Of a Annua On Response To Heat Shock And Uv Irradiationmentioning
confidence: 99%
“…There was about 1.89 fold increase in expression of sod-3 in worms treated with 100% A. annua extract, compared to the untreated worms (p < 0.001) (Figure 4b). A recent study shows that dietary supplementation of N-acetyl-L-cysteine results in extended survival time under heat-and oxidative-stress conditions, as well as reduced susceptibility to stresses that accompany the up-regulation of stress-responsive genes (Dh et al, 2015). Gene expression data obtained here support our hypothesis that supplementation of A. annua extract confers increased resistance to heat and oxidative stress in vivo and suggests that the underlying mechanisms may be involved with the induction of stress-responsive genes, including heat shock proteins and anti-oxidant genes.…”
Section: Induction Of Stress-responsive Genes By a Annuamentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts from Acanthopanax sessiliflorus stem shows a suppressive effect on oxidative DNA damage and increased survival under oxidativestress conditions (PARK et al, 2014). Interestingly, NAC, the other cysteine derivative, has strong antioxidant activity in vivo and induces the expression of anti-oxidant gene (OH et al, 2015). Therefore, further studies should focus on revealing underlying cellular mechanisms involved in increased resistance to oxidative stress by these cysteine derivatives.…”
Section: Sac Increases Resistance To Oxidative Stressmentioning
confidence: 99%
“…Coenzyme Q 10 promotes the recovery of heart tissue after aerobic stress and the contractile function after cardiac surgery (ROSENFELDT et al, 2002). A recent study reports that N-acetyl cysteine (NAC), a cysteine derivative having a strong anti-oxidant activity, can improve health span by increasing resistance to oxidative, heat, and ultraviolet (UV) stresses (OH et al, 2015).…”
Section: Introductionmentioning
confidence: 99%